PERAN AUDIT INTERNAL DALAM MENCEGAH FRAUD DI PERUSAHAAN - Nurul Tsalatsa Azizah; Rahmadina Rahmadina; Warda Mumtaza; Ratih Kusumastuti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
This study aims to analyze the role of internal audit in preventing fraud within the company. Fraud is an act of deception or manipulation that is carried out with the aim of gaining illegal profit, and can cause significant financial losses for the company. Internal audit, as an independent and objective function, is responsible for assessing the effectiveness of the internal control system and ensuring compliance with applicable policies and procedures. In this study, a qualitative approach was used by conducting literature studies and case analysis related to fraud in companies. The results of the analysis show that the role of internal audit is very important in preventing and detecting fraud within the company. Internal audit can help identify gaps or weaknesses in the internal control system, as well as provide recommendations to improve business processes that are vulnerable to fraud. Several strategies that can be carried out by internal audit in preventing fraud include assessing fraud risk, testing and evaluating internal control systems, checking transactions regularly, as well as educating and training employees regarding business ethics and corporate governance. In addition, internal audit can also act as a channel for complaints (whistleblowing) which allows employees to report fraud without fear of retaliation. This study concludes that internal audit has a crucial role in preventing and reducing the risk of fraud within a company. By conducting a comprehensive and proactive audit, internal audit can help create a business environment that is transparent, ethical and with integrity. The results of this study are expected to provide insights and recommendations for companies in optimizing the role of internal audit in preventing and managing fraud risk.